217k views
1 vote
Show two different ways to solve 2/3(3x+6)=4x+3

User Jcfollower
by
5.1k points

2 Answers

4 votes

Answer:

Sorry You are having trouble!

Explanation:

User Bryce Siedschlaw
by
4.7k points
5 votes

Answer:

In the two different ways we have solved the given equation as
x=(1)/(2)

Explanation:

Given expression is
(2)/(3)(3x+6)=4x+3

To simplify the given expression in two ways:

First way:

Given
(2)/(3)(3x+6)=4x+3


(2)/(3)(3x+6)=4x+3


(6x+12)/(3)=4x+3

Multiplying 3 on both sides


3* ((6x+12)/(3))=3* (4x+3)


6x+12=12x+9


6x+12-12x-9=0 (adding the like terms)


-6x+3=0


3(-2x+1)=0

Dividing by 3 on both sides


3(-2x+1)* \frac{1}3}=0* \frac{1}3}


(-2x+1)=0


-(2x-1)=0


2x-1=0


x=(1)/(2)

Therefore the given expression is solved that
x=(1)/(2)

Another way:

Given
(2)/(3)(3x+6)=4x+3


(2)/(3)(3x+6)=4x+3


2((3x)/(3)+(6)/(3))=4x+3


2(x+2)=4x+3


2x+4=4x+3


4x+3-2x-4=0 (adding the like terms)


2x-1=0


x=(1)/(2)

Therefore the given expression is solved that
x=(1)/(2)

In the two different ways we have solved the given equation as
x=(1)/(2)